2019
DOI: 10.5539/jas.v12n1p149
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control Associated With Plant Nutrition for Meloidogyne javanica and Pratylenchus brachyurus Management in Soybean

Abstract: Meloidogyne javanica and Pratylenchus brachyurus stand out among the main nematodes in soybean crops. Research on integrated management are often conducted, due to the low efficiency of the main control methods when they are applied alone. Thus, the aim of the present study was to assess the potential of biological control and plant nutrition products to control these nematodes in soybean. The effect of each product alone on nematode hatching and mortality was also assessed. A greenhouse experiment was also ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In general, the recommendation of biological control for phytoparasitic nematodes deserves caution since the microorganisms used as antagonists can suffer different environmental influences, such as soil temperature, pH, humidity, and the presence of chemical residues, which can derail the potential effects of biological control (Lopes et al, 2020;Oliveira et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the recommendation of biological control for phytoparasitic nematodes deserves caution since the microorganisms used as antagonists can suffer different environmental influences, such as soil temperature, pH, humidity, and the presence of chemical residues, which can derail the potential effects of biological control (Lopes et al, 2020;Oliveira et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Venkat Rao et al (1986) and Bawa et al (2014), Bello et al (2007), Elbardi et al (2008); Asif et al (2014), Sahu et al (2018), Akhtar et al (2019), El-Nuby and Alam (2020) and Mendes-Lopes et al (2020) found a significant effect of plants from the Fabaceae family (Fabace Lindl.) towards reducing the process of leaving eggs by second-stage juveniles of M. incognita and M. javanica.…”
mentioning
confidence: 95%